1996
DOI: 10.1016/s0022-5223(96)70249-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the size of aortic valve prostheses on hemodynamics and change in left ventricular mass: Implications for the surgical management of aortic stenosis

Abstract: We conclude that despite undeniable recent improvements in the design of artificial heart valves, 19 mm aortic prostheses continue to create significant obstruction of the left ventricular outflow tract and, possibly as a consequence of this, fail to bring about significant reduction in left ventricular hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
69
2
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 27 publications
5
69
2
4
Order By: Relevance
“…It is known that, LVMI decreases with the reduction of LV afterload after s-AVR and as a result, improvement in myocardial ischemia, functional capacity and long-term prognosis is observed [12,13]. The regression in LVMI after s-AVR is believed to be more important than valvular gradient as a prognostic factor [14][15][16]. The rate and magnitude of regression in LVMI can also be used as a distinctive parameter for reverse cardiac remodeling [17].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that, LVMI decreases with the reduction of LV afterload after s-AVR and as a result, improvement in myocardial ischemia, functional capacity and long-term prognosis is observed [12,13]. The regression in LVMI after s-AVR is believed to be more important than valvular gradient as a prognostic factor [14][15][16]. The rate and magnitude of regression in LVMI can also be used as a distinctive parameter for reverse cardiac remodeling [17].…”
Section: Discussionmentioning
confidence: 99%
“…4 It is expected that LV mass regression is greater with lower aortic valve pressure gradients after AVR. 5,6 However, the Placement of Aortic Transcatheter Valve (PARTNER) Trial using a balloon-expandable bovine pericardial aortic bioprosthesis demonstrated that LV mass regression was faster and greater after surgical aortic valve replacement (SAVR) compared to transcatheter aortic valve replacement (TAVR) despite higher aortic pressure gradients and more frequent patient-prosthesis mismatch (PPM) after SAVR. 7,8 The CoreValve US Pivotal Trial using a self-expanding valve in a larger number of patients with severe AS and high surgical risk 9 yielded a similar paradoxical finding of a faster and greater reduction of LV mass in the SAVR group when LV mass was calculated by a standard mass formula.…”
Section: Introductionmentioning
confidence: 99%
“…Em trabalho publicado por St. John Sutton et al 4 foi demonstrado melhora significativa na fração de ejeção em uma média de 6 semanas de pós-operatório de substi- Nas cirurgias de pacientes com estenose aórtica e anel aórtico pequeno, para evitar cirurgias com maior morbidade, tais como as de ampliação do anel aórtico, o cirurgião muitas vezes implanta próteses valvares menores, as quais geram maiores gradientes pressóricos transvalvulares no pós-operató-rio e menor regressão da hipertrofia ventricular esquerda 3,5 . Nesses pacientes, a valvoplastia aórtica torna-se uma alternativa com baixa morbidade, principalmente nos pacientes mais idosos.…”
Section: Discussionunclassified
“…O gradiente transvalvar médio pós-operató-rio neste estudo foi de 23,0±9,1 mmHg. Em trabalho publicado por Gonzáles-Juanatey et al 5 , em pacientes usando próteses valvares aórticas (biológicas e metálicas) de 19 mm, o gradiente transvalvar médio foi de 18,3±7 mmHg. Em outra publicação 3 o gradiente transvalvar médio pós-operatório foi de 18,2±4,6 mmHg ao se utilizar próteses biológicas de 21,4±0,9 mm e , ao se utilizar próteses metálicas de mesmo tamanho, esse gradiente foi de 15,7±3,8 mmHg.…”
Section: Discussionunclassified
See 1 more Smart Citation